Decision Making on Student Academic Achievement Assessment Using the Topsis Method - S Susliansyah; Aditia Dwinanto; Heny Sumarno; Hendro Priyono; Linda Maulida (IJISTECH (International Journal of Information System and Technology), 2021)
Student academic achievement is a very important matter for all school parties that are directly or indirectly related, especially for Depok Tourism Vocational School, student academic achievement is one of the benchmarks in the success of education. Currently, the process of determining student achievement from the academic side of the Depok Tourism Vocational School is still using a manual system, so it takes a long time to determine the assessment of student academic achievement, because there are quite a lot of student data recording. In addition, it is still less relevant because it has not used the right calculation method, resulting in inaccurate calculations. This research uses the Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) method, because this method is a simple concept and easy to understand and to help the optimal decision-making process to solve practical decision problems. The results of the research using the Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) method found that students with the name Akmal Adnanto got the first rank with the highest preference value of 0.760.